Analisis Ketidakpastian Durasi Menggunakan Metode PERT dan PDM Guna Mengantisipasi Risiko Pada Proyek Konstruksi - Divo Reynandra Hermanto; Lila Ayu Ratna Winanda; Deviany Kartika; Munasih Munasih (Universitas Batanghari Jambi, 2026)
Duration uncertainty is a major problem in construction projects because it has the potential to cause delays in implementation and increase the risk of rework. Time planning that uses only one duration estimate is often unable to represent the dynamic variations in field conditions, resulting in an unrealistic schedule. Therefore, a scheduling approach is needed that can accommodate duration uncertainty while systematically describing the relationships between activities. This study aims to analyze the duration uncertainty of work and identify critical activities in order to anticipate the risk of construction project delays. The research method used is the integration of the Program Evaluation and Review Technique (PERT) and the Precedence Diagram Method (PDM). Data was obtained through interviews, field observations, and technical project document studies to determine optimistic, most likely, and pessimistic duration estimates (a–m–b). These estimates were processed using the PERT method to calculate the expected time, standard deviation, and variance of activities, then arranged in a PDM work network to determine the critical path. The results showed that the expected project duration was 225 days, with the highest level of uncertainty found in the B3 floor 6 steel beam work, which had a variance value of 2.250. The accumulated standard deviation of the critical path is 13.88 days with a variance root value of approximately ±4 days, indicating the potential for project duration deviations from the planned schedule. Therefore, it is recommended that activities with high variance on the critical path receive more intensive time control and supervision to minimize the risk of project delays.